Control of contraction and relaxation of insect muscle using inhibitory-neurotransmitter encapsulated thermossensitive liposome - Lau, Edward Quan Feng (2018)
This project aims to study the inhibition of insect leg muscle via artificial means. Voluntary motion by the insect will be disabled with a simple trigger and allows the user to have more control over the insect. The key subject of study in this project is the Mecynorrhina Torquata beetle, or also known as the giant flower beetle. It is one of the largest known species of flower beetles in the world. Many previous research and developments on cyborg beetles use the M.Torquata as the subject. Gamma-aminobutyric acid, also known as GABA, is a known neurotransmitter will be used to induce the muscle inhibition. It will be delivered via a thermosensitive liposome that will encapsulate GABA until a critical temperature is met. Rapid cooling of the muscle is also part of this project in an attempt to stop excess GABA from releasing and used again for another inhibition cycle. Two different coolers are being compared for use and one will be chosen for the experiment where GABA is injected. Experimental results attained have shown that the cooler with dry ice is more ideal as it has a faster cooling rate and able to attain a lower temperature. GABA is also shown to take effect for approximately 3 hours and the leg muscles of the beetle is damaged on the second round of heating. Further studies are needed to improve the heating system to ensure less damage done to the beetle muscle and also improve the overall process of injection and activation of GABA to reduce human errors.